Coastal Family Communication Culture in the Case of Low Educational Quality Among Fishermen's Children (A Case Study of Fishermen Families in Bagan Kuala Village, Serdang Bedagai Regency) - Zuhdi, Abdurrahman; Adhani, Abrar; Lubis, Faizal Hamzah (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2026)
Introduction: This study looks at how family communication in fishermen households in Bagan Kuala Village affects the low quality of education among their children. Many fishing families focus more on work and income than on school, which impacts children's motivation to learn. The main issue is that communication about education is limited and often one-sided, with parents making decisions without much discussion. This topic is important because not many studies have explored how family communication, not just poverty, plays a role in children's education in coastal communities.Methods: The research uses a qualitative case study approach. Data were collected from five fishermen families through purposive sampling. In-depth interviews, direct observation, and documentation were used to explore communication patterns, and the data were analyzed thematically to identify meaningful insights.Results: Findings show that educational discussions are rarely prioritized in family communication, which tends to be one-directional from parents to children. Economic survival dominates decision-making, leading to weak motivation among children to pursue formal education. Only one family reported active dialogue about higher education.Conclusion: The study concludes that limited, economically driven communication within fishermen families contributes significantly to the low educational outcomes of children. This highlights the need for family-level communication interventions that emphasize the long-term value of education and empower both parents and children. The main takeaway is that improving educational quality in coastal communities requires addressing not only access and funding but also internal family dynamics and cultural values